Framing ideas for new venture resources acquisition in crises : An fsQCA analysis - Stroe, Silvia; Siren, Charlotta; Parida, Vinit; Wincent, Joakim (Elsevier, 2022)
How should new venture ideas be framed in order to acquire human resources and gain support in times of crisis characterized by struggling or failing institutions and governmental organizations? To answer this question, we analyze 316 new venture ideas aimed at alleviating the COVID-19 crisis in 11 countries. We investigate different linguistic framing configurations and test their persuasive power for human resource acquisition. Our fuzzy-set qualitative comparative analysis (fsQCA) and linguistic analysis reveal that a “common enemy framing” is crucial for obtaining resources in crisis contexts. Non-profit venture ideas, specifically, may acquire resources via two additional paths: adding positive emotional content or using an entrepreneurial hustle framing with concrete calls to action. Our findings provide novel insights into entrepreneurial resource acquisition and idea framing during crises.
Keywords: New venture ideas; Framing; Resource acquisition; fi=Strateginen johtaminen|en=Strategic Management|